2016
DOI: 10.1620/tjem.240.281
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes of Patients Treated for Pulmonary Tuberculosis after Undergoing Gastrectomy

Abstract: Gastrectomy is a proxy of malnutrition, which may lead to increased risk for developing pulmonary tuberculosis (TB). Malabsorption in gastrectomy patients could lead to low serum levels of rifampicin, which may be related to higher treatment failure. However, there is limited information on treatment outcomes of TB in patients who have undergone gastrectomy. This study aims to determine treatment outcomes and adverse effects in patients treated for TB after undergoing gastrectomy for gastric cancer. During the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…It was consistent with Kim et al, which found that immune suppression by the tumor increased vulnerability to reactivation of TB (Kim et al, 2008). Several studies from Taiwan and Korea have also identified gastric cancer as a significant risk factor for TB (Fang et al, 2015;Jung et al, 2016). The digestive organ in this study included esophagus, stomach, small intestine and other ill-defined digestive organs.…”
Section: Discussionsupporting
confidence: 91%
“…It was consistent with Kim et al, which found that immune suppression by the tumor increased vulnerability to reactivation of TB (Kim et al, 2008). Several studies from Taiwan and Korea have also identified gastric cancer as a significant risk factor for TB (Fang et al, 2015;Jung et al, 2016). The digestive organ in this study included esophagus, stomach, small intestine and other ill-defined digestive organs.…”
Section: Discussionsupporting
confidence: 91%
“…10,20 Numerous studies from Taiwan and Korea have also identified gastric cancer as an important risk factor for TB. 20,32,33 Since the digestive organs are important for nutrition, digestive organ dysfunction can lead to malnutrition and opportunistic infections. 20 Macrophages are a major component of TILs in gastrointestinal cancers.…”
Section: Discussionmentioning
confidence: 99%